NIR absorbing thiophene derivatives with photoacoustic and photothermal effect used in drug release. (March 2019) - Liu, Wenyan; Li, Bingnan; Gao, Hong; Wang, Dong; Wang, Lei; Yang, Zhou; Cao, Hui; He, Wanli; Wang, Hao; Zhang, Jingjing; Xing, Yan
Abstract: Small near-infrared (NIR) absorbing organic molecules are highly demanded for photoacoustic (PA) imaging and photothermal (PT) therapy recently. In this study, the PA imaging and PT effect of a novel series of small organic π-conjugated NIR absorbing thiophene derivatives, synthetized via click reaction, were characterized carefully. It was interesting to note that derivatives clicked by F4 -TCNQ showed a red shift of PA peaks, compared to those clicked by TCNQ. Besides, it turned out that the PA intensity and PT conversion efficiency of the series of NIR absorbing dyes were extremely high at a low concentration. Surprisingly, the PA values remained high when H43 molecules were loaded in liposomes in cells. To solve the problem that the liposomes behaved incapable of releasing drugs, H43, the representative one of the thiophene derivatives, was innovatively loaded together with Nile Red in temperature-responsive micelles, where H43 acted as a great photothermal conversion agent, induced the micelles to shrink when the NIR light irradiated and the maximum temperature of the solution was 32 °C. The cumulative release of H43 micelles was considerable in comparison to that immersed in 32 °C water bath. The systematical study of the organic NIR dyes provides a new strategy to design NIR absorbing dyes with high PA intensity and puts forward a fresh idea that NIR light stimulus could replace temperature stimulus of thermosensitive micelles by using NIR dyes to realize the combination of PA imaging, PT therapy and NIR-responsive drug release therapy. Highlights: The PA and PT conversion effect of the NIR absorbing dyes were extremely good. The PA effect of the NIR absorbing dyes in cells was still evident. The NIR absorbing dyes replaced the thermal stimulus in thermosensitive micelles. Combined treatment of PA imaging, PT therapy and drug release therapy was proposed.